2017
DOI: 10.2134/agronj2016.07.0440
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Miscanthus and Switchgrass Cultivars for Biomass Yield, Soil Nutrients, and Nutrient Removal in Northwest Spain

Abstract: Comparative performance tests of perennial grasses for biomass yield, quality, and soil nutrient removal are needed to guide decisions toward meeting European Union targets for renewable energy production. We compared hybrid miscanthus (Miscanthus × giganteus Greef and Deuter ex Hodkinson and Renvoize) and switchgrass (Panicum virgatum L.) cultivars Cave-in-Rock, (upland type), Alamo, and Kanlow (lowland types) for biomass yield and changes in soil macronutrient levels and removal rates in a humid Spanish envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
3
17
2
1
Order By: Relevance
“…On average, Alamo switchgrass cultivar under irrigated conditions removed 28.5 to 35.7 g N m −2 , 2.52 to 3.48 g P m −2 , and 29.6 to 38.4 g K m −2 per yr. No significant differences were observed in macronutrients (N, P, and K) uptake among different treatments except for the freshwater‐gypsum combination, which was lower than the other treatments. Macronutrients uptake by switchgrass in our study was higher than that reported for other cultivars of switchgrass grown under rainfed conditions (Ashworth, Rocateli, West, Brye, & Popp, ; Oliveira, West, Afif, & Palencia, ). However, our results were comparable to macronutrient removal under two‐cut harvest system of switchgrass under either rainfed (Kering, Butler, Biermacher, Mosali, & Guretzky, ) or freshwater irrigation (Kimura, Collins, & Fransen, 2015).…”
Section: Resultscontrasting
confidence: 81%
See 1 more Smart Citation
“…On average, Alamo switchgrass cultivar under irrigated conditions removed 28.5 to 35.7 g N m −2 , 2.52 to 3.48 g P m −2 , and 29.6 to 38.4 g K m −2 per yr. No significant differences were observed in macronutrients (N, P, and K) uptake among different treatments except for the freshwater‐gypsum combination, which was lower than the other treatments. Macronutrients uptake by switchgrass in our study was higher than that reported for other cultivars of switchgrass grown under rainfed conditions (Ashworth, Rocateli, West, Brye, & Popp, ; Oliveira, West, Afif, & Palencia, ). However, our results were comparable to macronutrient removal under two‐cut harvest system of switchgrass under either rainfed (Kering, Butler, Biermacher, Mosali, & Guretzky, ) or freshwater irrigation (Kimura, Collins, & Fransen, 2015).…”
Section: Resultscontrasting
confidence: 81%
“…Macronutrients uptake by switchgrass in our study was higher than that reported for other cultivars of switchgrass grown under rainfed conditions (Ashworth, Rocateli, West, Brye, & Popp, 2017;Oliveira, West, Afif, & Palencia, 2017). However, our results were comparable to macronutrient removal under two-cut harvest system of switchgrass under either rainfed (Kering, Butler, Biermacher, Mosali, & Guretzky, 2013) or freshwater irrigation (Kimura, Collins, & Fransen, 2015).…”
Section: Significant Influence Of Growth Year On Nutrient Concentrationscontrasting
confidence: 61%
“…Differences between the two ecotypes were evident only in Italy, with the lowlands leading to improved productive performance, even if the lack of replicates makes this result in need of further confirmation. This finding corroborated results reported by [4,6,30] under similar climatic conditions, as well as those obtained by [13] and [38] under different locations across the USA. The lowland ecotypes, despite being later than the upland ones, benefited from the prolonged length of the growing season under the Mediterranean climate, where temperatures remain above 10 • C for the whole year and above 14 • C in the April-to-September period.…”
Section: Discussionsupporting
confidence: 92%
“…A tiller density ranging between 800 to 1000 tillers m −2 is often reported as optimal in switchgrass for the control of weed pressure [35,36]. The adoption of irrigation should also be wisely considered in terms of management costs [11], but in semi-arid areas, like the southern part of the Mediterranean basin, it is often essential in order to achieve adequate yield, as extensively reported by [37][38][39]. The surveyed values for biomass yield in Greece were in line with those found in studies carried out under the same [4] or similar conditions [6,30,36] but generally lower than those reported by [13] in a 20-year trial in Alabama (USA), where precipitation during the growing season often exceeded 900 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to efficient biomass production, which has very good combustion quality (Cvetković et al, 2016;Bilandžija et al, 2017), miscanthus should give a significant contribution to sustainable agricultural production of combustible biomass in the near future (Dohleman et al, 2012;Mishra et al, 2013;Perić et al, 2018a). The high yield of miscanthus, together with its relatively low macronutrient concentrations and intermediate removal rates, indicates its advantages over other grasses as a biomass crop choice (Oliveira et al, 2017). Along with profitability, it is estimated that the energy production based on miscanthus cultivation will also contribute to the multi-functionality of agriculture (Daraban et al, 2015).…”
Section: Introductionmentioning
confidence: 99%